Re-Education and the Construction of Whiteness in the US Military - Gerund, Katharina (Comparativ, 2021)
This article examines processes of re-education with regard to their racial regimes epitomized in discourses on race and racism in the US military toward the end of World War II and during the early days of the US-American presence in post-war Germany. It teases out the role of whiteness and white privilege, which is constructed via-à-vis a black Other, at the centre of the US military mission in Europe (and beyond) and shows how the war effort and the (planning of) the occupation and re-education/reorientation of Germany prompted a reflection on racial inequality within the US Army (and US society at large). This potential of internal reform and self-conscious re-education under the guise of managing manpower and bolstering efficiency abroad, however limited in its actual influence on mitigating racism and challenging white he- gemony, bespeaks the (unintended) effects of re-education at home, even prior to the official programmes targeting the German populatio